The erasures of racism in education and international development: re-reading the 'global learning crisis'. Issue 5 (3rd July 2020) - Sriprakash, Arathi; Tikly, Leon; Walker, Sharon
ABSTRACT: Despite pervasive forms of racism on a global scale, the field of education and international development continues to fail to substantively engage with the production and effects of racial domination across its domains of research, policy and practice. Considerations of racism remain silent, or indeed, are erased, within teaching and research, often in favour of colour-blind and technocratic approaches to 'development'. This not only ignores the sector's historical links to systems of racial domination, but also the current ways in which the field is implicated in producing unequal outcomes along racial lines. The authors present a re-reading of the 'global learning crisis' – as the dominant discourse of contemporary educational development – to demonstrate how the framing of the 'crisis' and the responses it engenders and legitimises operate as a 'racial project'. The paper offers theoretical and methodological resources with which to interrogate the field's entanglements in systems of racial domination and challenge its erasures of racism.